2019
DOI: 10.3389/fphy.2019.00013
|View full text |Cite
|
Sign up to set email alerts
|

Weak Quasielastic Hyperon Production Leading to Pions in the Antineutrino-Nucleus Reactions

Abstract: In this review, we have studied the quasielastic production cross sections and polarization components of Λ, Σ 0 and Σ − hyperons induced by the weak charged currents in the antineutrino reactions on the nucleon and the nuclear targets like 12 C, 16 O, 40 Ar and 208 Pb. It is shown that the energy and the Q 2 dependence of the cross sections and the various polarization components can be effectively used to determine the axial vector transition form factors in the strangeness sector and test the validity of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 103 publications
0
8
0
Order By: Relevance
“…For details, please see Ref. [407,408]. Historically, the axial vector form factor g 1 (q 2 ) has been parameterized as a dipole given by…”
Section: Quasi-elastic Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…For details, please see Ref. [407,408]. Historically, the axial vector form factor g 1 (q 2 ) has been parameterized as a dipole given by…”
Section: Quasi-elastic Scatteringmentioning
confidence: 99%
“…These nuclear medium effects play an important role in the final state composition, in interpreting the experimental results, and in the determination of M A in nuclear target data. It has been also observed that the quasi-elastic hyperon production induced by antineutrino scattering can give significant contribution to the pion production arising due to the hyperon decay and is comparable to the pions arising due to ∆ decay in nuclear targets in the sub-GeV energy region relevant for atmospheric and accelerator experiments being performed to study neutrino oscillation phenomenona [407,[411][412][413].…”
Section: Cross Sections and Polarization Observables In Quasi-elastic...mentioning
confidence: 99%
“…It is worth noticing that Eqs. (8) and (9) are generally expressed for the SU (3) couplings. However, it has been shown by previous authors [3,4] that such relationships work well for finite q 2 too.…”
Section: Transition Form Factors For Non-resonant Backgroundmentioning
confidence: 99%
“…In last decade there were several attempts to explore the strangeness physics in weak sector [1,2]. The quasielastic production of hyperons [3][4][5][6] and their subsequent decay into pions [7,8] have been recently analyzed around ∼ 1 GeV anti-neutrino energies. Experimental efforts are also made to observe such processes [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we study the effect of using various parametric forms of the weak vector and axial vector form factors as well as the effect of pseudoscalar and second class current form factors in the axial vector sector on the total cross section, differential cross section and the polarization components of τ leptons produced in the quasielastic ν τ (ν τ )−nucleon scattering following our earlier works in the case of ν µ (ν µ )−nucleon scattering [17,[41][42][43]. In section II, we define the matrix element in terms of the various weak form factors and describe their properties under symmetry transformations and express the differential cross sections in terms of these form factors.…”
Section: Introductionmentioning
confidence: 99%